Physical and chemical variables analysis for clustering of soils in the longitudinal dunes of Sandy Pampa, Argentina - Irigoin, Julieta; Paladino, Ileana Ruth; Civeira, Gabriela; Costa, María Cristina (Springer, 2018)
The Sandy Pampa landscape was built on ancient dune-shaped landforms, which persist today and affect the characteristics of the soil in different sectors of the dunes. Based on their topographic position, different soils were developed. The objectives of this study were: (1) to determine the degree of heterogeneity between soils in the region, classified at taxonomic subgroup level according to their physical and chemical properties and (2) to identify the most sensitive properties in order to differentiate soils for management purposes. Physical and chemical properties of representative soils were studied using cluster analysis, principal component analysis and variance analysis. The results showed that soils can be paired off with reference to their topographic location and less related to the taxonomic classification. The variables with the highest incidence to differentiate soils were: sand content, exchangeable calcium, pH paste and exchangeable sodium percentage. These variables have a great impact on the definition of physical and chemical behavior of soils.